DETERMINASI PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI NANGGROE ACEH DARUSSALAM - Mahdawi, Mahdawi; Rustam, Rinaldi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of Special Autonomy Fund, Regional Tax, Personnel Expenditure, Goods and Services Spendingand Human Development Index on Gross Regional Domestic Product of regency/municipality in Nanggroe Aceh Darussalam Province from 2015 to 2019. This study used quantitative descriptive method. The research model used was an econometric model measured using panel data regression. The results of panel data regression showed that the selected model is a fixed effect model. The results found that partially, only the variable of goods and services spending has no significant effect on gross regional domestic product. Meanwhile, the variables of special autonomy fund and personnel expenditure have a negative effect on gross regional domestic product. Meanwhile, regional tax and human development index have a positive significant effect on gross regional domestic product. The variables of special autonomy fund, local tax, personnel expenditure, goods and services spending, and human development index simultaneously have a significant effect on gross regional domestic product of regency/municipality in Nanggroe Aceh Darussalam Province.